Is Lecture as a Dominant Form of Teaching Dying? - N. N. Gubanov; N. I. Gubanov (Высшее образование в России)
The article is devoted to the actively debated, difficult and for many teachers a painful problem addressing lecture as a dominant form of teaching. Nowadays, lecture is increasingly seen as an inefficient form of education, hopelessly outdated, with little interest and response among students, useless and, in principle, dying. The authors are firmly convinced that lecture was, continues to be and will be the main and indispensable form of instruction for the reproduction of an intellectual elite. To substantiate this position, the article presents an argumentation system that unfolds in three stages. In the first part of the article, the essence of lecture is revealed in the light of Randall Collins' theory of intellectual interactive rituals. The subject's intellectual creativity is conditioned by his personal contacts “face to face” with other intellectuals, as well as the position of this subject in the intellectual network. There is a demonstration that lecture has all the hallmarks of an interactive ritual, and it is its archetypal case, which ensures the transmission of cultural capital from the older generation of intellectuals to the young one. During this process, its successful participants feel surge of emotional energy necessary for intellectual creativity. In the second part of the article, the distinctive positive aspects of lecture are systematized and discussed, which together make it a unique form of training that gives indispensable experience to both lecturer and participants. The third part of the article, based on the real history of education and providing illustrative examples, is a kind of empirical confirmation of the first two parts. The article may be of interest to teachers, students, as well as anyone who is not indifferent to the current state of education in Russia.